Peran dan Fungsi DPRD Provinsi Kalimantan Tengah dalam Mewujudkan Good Governance - Nadia Khairunnisa; Siti Hairunisa; Ana Tiara Yuliandari; Nor Putri Prasiska; Astiara Astiara (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study discusses the Function of the Central Kalimantan DPRD Secretariat in the realization of good governance. In the context of regional autonomy, this article explains the role of local governments in improving community welfare through effective public services. Local governments are given the authority to regulate government affairs to achieve community welfare through improved services and public participation. Based on Law No. 32 of 2004 and Law No. 23 of 2014, the role between the local government and the DPRD is explained, where the regional head is responsible for the implementation of the government and the DPRD carries out the functions of legislation, supervision, and budget. Public service is an important aspect of the government bureaucracy, which reflects a commitment to bureaucratic reform. This research also explores the concept of good local governance which is increasingly becoming a demand of the community, as well as the role of the government, the private sector, and the community in realizing it. Special focus is given to the Secretariat of the Central Kalimantan Provincial Parliament in optimizing its functions to support the implementation of good governance. The method used is empirical juridical, which combines legal aspects with direct observation in the field. The results of the study show that the Secretariat of the Central Kalimantan Provincial Parliament has an important role in realizing the principles of good governance, including transparency, accountability, and public participation. Thus, good government management can improve the quality of life of the community in general.